Kesenian Badud dalam Upacara Panen di Desa Margacinta Kecamatan Cijulang Kabupaten Pangandaran - Prayogo Pangestu; Cepi Irawan (Jurnal Mebang: Kajian Budaya Musik dan Pendidikan Musik, 2026)
This research aims to reveal the symbolic meanings contained in the Badud performing art during the harvest ceremony in Margacinta Village, Cijulang District, Pangandaran Regency. The focus of the study is directed toward the musical elements, dance, costumes, and ritual sequence that shape the structure of the Badud performance as part of the agrarian traditions of the local community. This study employs a qualitative method with an ethnomusicological approach, which integrates musical analysis with socio-cultural contexts to understand function, structures, and meaning of Badud I community life. Data were collected through direct observation of the Badud performance, audio-visual recording, and in-depth interviews with cultural figures, artists, and community leaders. The data analysis technique uses the interactive model of Miles and Huberman (data reduction, data display, and conclusion drawing), strengthened by Roland Barthes semiotic theory to explore denotative, connotative, and mythical meanings within the symbolic elements of the performance. The findings show that Badud contains agrarian symbols related to hopes for fertility, protection of crops, and expressions of gratitude for the harvest. The music of dog-dog, angklung, and kempul creates a ritual atmosphere believed to repel pests, while the animal costumes represent the dynamics of nature and the relationship between humans and cosmological forces. Overall, Badud functions as both a ritual medium and a cultural identity that reflects the spiritual values and everyday life of the Margacinta community.